After the Arab Spring. (May 2014) - Walzer, Michael
In order to answer the question, Can there be a democratic revolution and a religious revival in the same place, at the same time?, I look at a number of 20 th -century cases (and several 18 th -century cases) where religion and radical politics interacted – with very different results.